2017
DOI: 10.1177/1948550616683017
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Implicit Gender-Science Stereotype? Exploring Correlations Between the Gender-Science IAT and Self-Report Measures

Abstract: Implicit measures of the gender-science stereotype are often better than explicit measures in predicting relevant outcomes. This finding could reflect a discrepancy between implicit and explicit stereotypes, but an alternative is that the implicit measure is sensitive to constructs other than the stereotype. Analyzing an archival data set (total N = 478,550), we found that self-reported liking of science versus liberal arts was the best predictor of the gender-science implicit association test (IAT). In a rean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
2
22
1
Order By: Relevance
“…In line with this idea, implicit and explicit attitudes have been shown to be more highly correlated with each other when participants were instructed to focus on their feelings rather than their thoughts (39)(40)(41). Moreover, at least under some conditions, implicit beliefs seem to be more closely related to explicit attitudes than they are to explicit beliefs (42). Finally, a recent investigation using a reinforcement learning perspective has found that whereas implicit attitudes track a history of personally experienced rewards and punishments, explicit attitudes also reflect additional information about the structure of the environment (43).…”
mentioning
confidence: 82%
“…In line with this idea, implicit and explicit attitudes have been shown to be more highly correlated with each other when participants were instructed to focus on their feelings rather than their thoughts (39)(40)(41). Moreover, at least under some conditions, implicit beliefs seem to be more closely related to explicit attitudes than they are to explicit beliefs (42). Finally, a recent investigation using a reinforcement learning perspective has found that whereas implicit attitudes track a history of personally experienced rewards and punishments, explicit attitudes also reflect additional information about the structure of the environment (43).…”
mentioning
confidence: 82%
“…Our SMP‐based measure has several advantages over existing IAT‐based measures of gender stereotyping (see Zitelny et al, ). As explained in detail by Teige‐Mocigemba et al (), the blocked task‐structure of the IAT has been linked to various sources of systematic measurement error that can undermine its construct validity.…”
Section: Discussionmentioning
confidence: 99%
“…Although various paradigms have been used to assess gender stereotyping (e.g., Banaji & Greenwald, ; Banaji & Hardin, ; Blair, Ma, & Lenton, ), the implicit association test (IAT; Greenwald, McGhee, & Schwartz, ) is by far the most popular one among the available options. The IAT has been used to measure various types of gender stereotypical associations, including male–science versus female–arts (Nosek, Banaji, & Greenwald, ; Nosek et al, ; for a review, see Zitelny, Shalom, & Bar‐Anan, ), male–strength versus female–weakness (Blair et al, ; Milne & Grafman, ), male–engineer versus female–teacher (White & White, ), and male–career versus female–household (Gawronski, Ehrenberg, Banse, Zukova, & Klauer, ). IAT‐measured math–gender stereotypes were found to predict academic self‐concepts, academic achievement, and enrollment preferences in 9‐year old girls (Steffens, Jelenec, & Noack, ).…”
mentioning
confidence: 99%
“…The belief that working in IS is a masculine endeavor (Cory et al, 2006;Fuller et al, 2013;Joshi & Schmidt, 2006;Lang, 2012;Sax et al, 2017;Serenko & Turel, 2016;Stout et al, 2016;Zitelny et al, 2017). These studies found that both men and women attribute such "masculine" characteristics of IS careers as isolation from other people, focus on self-promotion rather than group communion, lack of empathy, and aggression.…”
mentioning
confidence: 97%
“…These studies have found that parental influence, role models, stereotypes, knowledge of the field, influence of peers, self-efficacy, and external encouragement are important factors that affect women's interest in IS. Recent studies that have examined implicit stereotypes to understand whether people implicitly relate technology to gender and also whether implicit gender identity predicts female interest in IS have found that implicit gender identity may guide "career choice" (Serenko & Turel, 2016;Stout et al, 2016;Zitelny, Shalom, & Bar-Anan, 2017).…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%